2013
DOI: 10.1177/0269215512473136
|View full text |Cite
|
Sign up to set email alerts
|

Subject-chosen activities in occupational therapy for the improvement of psychiatric symptoms of inpatients with chronic schizophrenia: a controlled trial

Abstract: The results suggested that the subject-chosen activities in occupational therapy could improve the psychiatric symptoms, suspiciousness, and preoccupation of the inpatients with chronic schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 14 publications
1
8
0
3
Order By: Relevance
“…Although there were not statistically significant differences in symptoms as measured by PANSS across treatment groups in this study, effect sizes of the change between groups were observed from small to large in the each domain including positive symptom, negative symptom, general psychopathology, and total score in PANSS. Our previous study of GOT + IOT demonstrated significant improvements in positive subscale, general psychopathology subscale, and total score in PANSS [ 18 ], and other previous studies reported that OT had beneficial effects on symptoms of patients with schizophrenia [ 16 , 17 ]. More studies are needed to evaluate the impact of OT on symptom of schizophrenia.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although there were not statistically significant differences in symptoms as measured by PANSS across treatment groups in this study, effect sizes of the change between groups were observed from small to large in the each domain including positive symptom, negative symptom, general psychopathology, and total score in PANSS. Our previous study of GOT + IOT demonstrated significant improvements in positive subscale, general psychopathology subscale, and total score in PANSS [ 18 ], and other previous studies reported that OT had beneficial effects on symptoms of patients with schizophrenia [ 16 , 17 ]. More studies are needed to evaluate the impact of OT on symptom of schizophrenia.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies have examined the effects of OT on patients with schizophrenia. Many of these reported that OT can improve symptoms, and combined interventions of OT and pharmacological treatment can more effectively improve symptoms than pharmacological treatment alone [ 16 , 17 ]. However, the effectiveness of OT for cognitive impairment in patients with schizophrenia has not been sufficiently verified.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have examined the effects of OT on patients with schizophrenia. Many of these reported that OT can improve symptoms, and combined interventions of OT and pharmacological treatment can more effectively improve symptoms than pharmacological treatment alone (Foruzandeh and Parvin, ; Hoshii et al, ). However, the effectiveness of OT for cognitive impairment in patients with acute schizophrenia has not been sufficiently verified.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Patients with chronic (but not acute) mental disorders have been successfully treated with occupational therapy, as a form of psychosocial therapy. [3][4][5] In Japan, occupational therapy has been recently tried in an attempt to improve the functioning of patients with acute mental disorders, 6 but the evidence of the feasibility and effects of occupational therapy are still limited. There have been no controlled clinical trials investigating the effect of early intervention with occupational therapy in people with acute psychosis.…”
Section: Introductionmentioning
confidence: 99%